2019
DOI: 10.1093/femsle/fnz230
|View full text |Cite
|
Sign up to set email alerts
|

Role of non-PTS dependent glucose permease (GlcU) in maintaining the fitness cost during acquisition of nisin resistance by Enterococcus faecalis

Abstract: Nisin is used for food preservation due to its antibacterial activity. However, some bacteria survive under the prevailing conditions owing to the acquisition of resistance. This study aimed to characterize nisin-resistant E. faecalis isolated from raw buffalo milk and investigate their fitness cost. FE-SEM, biofilm and cytochrome-c assay were used for characterization. Growth kinetics, HPLC, qPCR, and western-blotting were performed to confer their fitness cost. Results revealed that nisin-resistant E. faecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…1658003) from Biorad was used for PAGE and blotting was performed using semi-dry blotting unit (Scie-Plas Ltd., UK). Sensitive and resistant E. faecalis (Nis R -147) bacteria were previously isolated from raw buffalo milk in our lab [ 5 , 23 ]. The nisin-resistant strain used here was found to be resistant to chloramphenicol, ampicillin, ciprofloxacin, rifampicin, vancomycin, carbenicillin, linezolid, oxacillin, and fosfomycin with minimum inhibitory concentrations (MICs) varying between 4 µg/mL (ciprofloxacin) and 512 µg/mL (fosfomycin) [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1658003) from Biorad was used for PAGE and blotting was performed using semi-dry blotting unit (Scie-Plas Ltd., UK). Sensitive and resistant E. faecalis (Nis R -147) bacteria were previously isolated from raw buffalo milk in our lab [ 5 , 23 ]. The nisin-resistant strain used here was found to be resistant to chloramphenicol, ampicillin, ciprofloxacin, rifampicin, vancomycin, carbenicillin, linezolid, oxacillin, and fosfomycin with minimum inhibitory concentrations (MICs) varying between 4 µg/mL (ciprofloxacin) and 512 µg/mL (fosfomycin) [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…The crude sample was loaded on 12% SDS-PAGE without heating. Anti-phosphoserine antibody was used to detect the serine phosphorylation of the HPr protein as described in [ 23 ]. The experiment was performed in triplicate and relative density was analysed using ImageJ (1.51v 9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both Staphylococcus aureus (58) and Streptococcus pyogenes (59), GlcU has been shown to contribute to glucose uptake under low affinity conditions, and a GlcU homolog is also present in the V583 genome (ef0928). Recent work by Kumar et al (60) showed that GlcU expression compensates for PTS-dependent glucose transport when E. faecalis is exposed to the lantibiotic nisin. Their findings indicated that glucose was shuttled through the pentose phosphate shunt pathway under GlcU-dependent conditions, as opposed to the conventional glycolytic pathway.…”
Section: Figmentioning
confidence: 99%
“…CHCC13235 has an SNP in a gene annotated as EAM type sugar transporter (glcU) (302C to 302T, resulting in amino acid change V101A). GlcU encodes a novel non-PTS glucose permease (Castro et al, 2009), which previously has been shown to play a role in fitness cost in nisin-resistant variants of Streptococcus faecalis (Kumar et al, 2019). In addition, CHCC13235 carries an SNP in the promoter region upstream of a LacI type regulator potentially regulating the neighboring gene maltodextrin phosphorylase, whose role in milk fermentations is unknown but was previously found to be upregulated in S. thermophilus under acidic growth conditions (Wu et al, 2019).…”
Section: Analysis Of Genetic Changes In Streptococcus Thermophilus Strains Resistant To D-cycloserinementioning
confidence: 99%